Pengaruh Motivasi Kerja Dan Pengawasan Internal Terhadap Kinerja Guru Sekolah Dasar - Lucia A. M. Patti (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study uses a quantitative approach while the method used is a survey method. The purpose of this study was to determine whether there is an effect of one variable with other variables using regression analysis, both partial regression and multiple regression. The results of hypothesis I conclude that internal control has a significant effect on the performance of elementary school teachers in Malalayang District, Manado City, which is proven to be significant. The coefficient of determination Y is R2 x 100% = 39.9% meaning that 39.9% of the performance of elementary school teachers in Malalayang District, Manado City is determined by internal supervisors. The results of hypothesis II, where the conclusion is that there is a significant influence between work motivation and the performance of elementary school teachers in Malalayang District, Manado City. The value of the correlation coefficient R = 0.508 and the coefficient of determination R Square = 0.244. So the coefficient of determination Y = R2 x 100% = 0.244 x 100% = 24.4% means that 24.4% of the performance of elementary school teachers in Malalayang District, Manado City is determined by the work motivation of elementary school teachers. The result of hypothesis III states that from the summary model data, an R value of 0.735 is obtained with a significance probability value (Fchange = 0.000). Because the significance value of Fchange <0.05, H1 is accepted, meaning that internal control and work motivation are simultaneously and significantly related to the performance of elementary school teachers in Malalayang District, Manado City.